'Ideally' unstable current sheets and the triggering of fast magnetic reconnection. (October 2016) - Tenerani, A.; Velli, M.; Pucci, F.; Landi, S.; Rappazzo, A. F.
Abstract : Magnetic reconnection is thought to be the dynamical mechanism underlying many explosive phenomena observed both in space and in the laboratory, although the question of how fast magnetic reconnection is triggered in such high Lundquist ( S ) number plasmas has remained elusive. It has been well established that reconnection can develop over time scales faster than those predicted traditionally once kinetic scales are reached. It has also been shown that, within the framework of resistive magnetohydrodynamics (MHD), fast reconnection is achieved for thin enough sheets via the onset of the so-called plasmoid instability. The latter was discovered in studies specifically devoted to the Sweet–Parker current sheet, either as an initial condition or an apparent transient state developing in nonlinear studies. On the other hand, a fast tearing instability can grow on an ideal, i.e. S -independent, time scale (dubbed 'ideal' tearing) within current sheets whose aspect ratio scales with the macroscopic Lundquist number as L/aS^1/3 – much smaller than the Sweet–Parker one – suggesting a new way to approach to the initiation of fast reconnection in collapsing current configurations. Here we present an overview of what we have called 'ideal' tearing in resistive MHD, and discuss how the same reasoning can be extended to other plasma models commonly used that include electron inertia and kinetic effects. We then discuss a scenario for the onset of 'ideal' fast reconnection via collapsing current sheets and describe a quantitative model for the interpretation of the nonlinear evolution of 'ideally' unstable sheets in two dimensions.